The Depiction of Abandoned and Lamenting Women in Catullus, Vergil and Ovid - Olfman, Heva (My University, 2021)
My study focusses on the laments expressed by Ariadne and Dido in the poems of Catullus, Vergil and Ovid. My study examines the evolution of the character type of the lamenting woman from its Greek origins and portrayal to its presentation in Catullus 64, Aeneid 4 and Heroides 7 and 10. The scholarship and theories of Elizabeth Harvey, Rebecca Armstrong, Bridgitte Libby, Laurel Fulkerson and Sharon James were essential for my understanding and interpretation of these poems. I also consider the implications of male poets writing ventriloquized female voices. Over the course of three chapters, I argue that each of these authors contributes to the development and establishment of a new Romanized theme of the seduced and abandoned lamenting woman and character type. It is evident in each depiction of Ariadne and Dido that the authors build on the standard characterizations in Greek epic and tragedy, and that from these models a new type of lamenting woman emerged. With this project I intend to make a contribution to our understanding of the issues involved in the poetic portrayal of male and female voices in the context of the classical literary tradition of lamenting.
Keywords: Latin Literature; Lamenting; Abandoned; Catullus, Vergil and Ovid